2017
DOI: 10.1136/bmjpo-2017-000147
|View full text |Cite
|
Sign up to set email alerts
|

Predicting tacrolimus concentrations in children receiving a heart transplant using a population pharmacokinetic model

Abstract: ObjectiveImmunosuppressant therapy plays a pivotal role in transplant success and longevity. Tacrolimus, a primary immunosuppressive agent, is well known to exhibit significant pharmacological interpatient and intrapatient variability. This variability necessitates the collection of serial trough concentrations to ensure that the drug remains within therapeutic range. The objective of this study was to build a population pharmacokinetic (PK) model and use it to determine the minimum number of trough samples ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Due to the differences between adults and children, PK parameters, CL/F (9.5 L/h) and V (233 L) were significantly lower than those in this model. 13 In this study, tacrolimus clearance was found to vary with POD and the co-administration of WZ capsules; distribution volume was significantly influenced by BW. POD is a significant covariate with high recognition among various studies.…”
Section: Discussionmentioning
confidence: 65%
“…Due to the differences between adults and children, PK parameters, CL/F (9.5 L/h) and V (233 L) were significantly lower than those in this model. 13 In this study, tacrolimus clearance was found to vary with POD and the co-administration of WZ capsules; distribution volume was significantly influenced by BW. POD is a significant covariate with high recognition among various studies.…”
Section: Discussionmentioning
confidence: 65%
“…This study developed a population pharmacokinetics (PopPK) model of tacrolimus in pediatric hematopoietic stem cell transplant (HSCT) patients and devised model-guided dosage regimens. One-compartment models with and without lag time have been reported for pediatric patients of different translation types, including lung, kidney, and heart ( Sam et al, 2000 ; Fukudo et al, 2006 ; Guy-Viterbo et al, 2014 ; Lu et al, 2015 ; Rower et al, 2017 ; Andrews et al, 2018 ). In this study, a one-compartment model without lag time was selected.…”
Section: Discussionmentioning
confidence: 99%
“…Different concomitant medications in immunosuppressant regimens after HSCT transplantation could have an impact on the pharmacokinetics of tacrolimus by affecting the action of CYP3A4 or P-gp, such as voriconazole, itraconazole, and posaconazole ( Cervelli and Russ, 2003 ; Rower et al, 2017 ; Huang et al, 2020 ). In our investigation, concomitant voriconazole use was found to be a major covariate that explains interindividual variability in tacrolimus CL, which is consistent with other PopPK studies.…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus is a calcineurin inhibitor commonly used for the prevention of acute graft-versus-host disease (aGVHD), defined as GVHD that occurs within 100 days post-transplant (3). To date, there are very limited studies examining the pharmacokinetic (PK) profile of tacrolimus in children post solid organ transplant (4,5). These pharmacokinetic studies have demonstrated significant interpatient variability in drug exposure.…”
Section: Introductionmentioning
confidence: 99%
“… 3 To date, there are very limited studies examining the pharmacokinetic (PK) profile of tacrolimus in children post solid organ transplant. 4 , 5 These PK studies have demonstrated significant interpatient variability in drug exposure. The oral bioavailability of tacrolimus in children ranges even more widely from 5% to 93%, with a mean bioavailability of 25% in patients who have undergone solid organ transplantation.…”
Section: Introductionmentioning
confidence: 99%